Deformation effects in giant monopole resonance - Kvasil, J.; Nesterenko, V. O.; Repko, A.; Bozik, D.; Kleinig, W.; Reinhard, Paul-Gerhard (Journal of Physics: Conference Series, 2015)
The isoscalar giant monopole resonance (GMR) in Samarium isotopes (from spherical 144Sm to deformed 148-154Sm) is investigated within the Skyrme random-phase- approximation (RPA) for a variety of Skyrme forces. The exact RPA and its separable version (SRPA) are used for spherical and deformed nuclei, respectively. Consistently with earlier investigations, the quadrupole deformation is shown to yield two effects: the GMR broadens and attains a two-peak structure due to the coupling with the quadrupole giant resonance.
CRIS-Team Scopus Importer:2023-07-24